Identifying the Role of Stakeholders in Occupational Safety and Health of Beauty Salon Businesses in Semarang Regency (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2019)
Beauty salon businesses continue to develop within the community, along the times and generation. Beauty salon is a public place that has the risk of disease transmission, environmental pollution or other health problems. To make a healthy environmental quality, either from the physical, chemical, biological, and social aspect that enable people to achieve the highest level of health, the role of stakeholders is needed to improve Occupational Safety and Health (OSH) in the beauty salon business. This research aims to identify the role of stakeholders in improving OSH in the beauty salon business in Semarang Regency. This study is an observational study with qualitative methods. The approach method is by conducting in-depth interviews with stakeholders on the improvement of OSH in beauty salons in Semarang Regency in March-May 2019. The result of the research describes that the stakeholder roles and status are categorized into main stakeholders (primary), supporting stakeholders (secondary) and key stakeholders. OSH in beauty salon business in Semarang Regency needs to be improved. This requires participation from related stakeholders, including the Health Office, Tourism Office, National Agency of Drug and Food Control/BPOM, beauty organizations, beauty salon owners, employees and customers.